Statistical and analytical aspect of the construction industry development - Stetsenko, S.; Bolila, N.; Moholivets, A.; Gavrilyuk, V. (Ways to Improve Construction Efficiency, 2020)
A study of the economic stability of construction companies at the sectoral level identified trends in changes in the structure of construction as a macroeconomic sector, the volume of income from construction activities, assets and liabilities of enterprises of various sizes. In order to study the changes in the level of sectoral competition, the dynamics of the structure of the distribution of construction enterprises by size was studied. For the final conclusion on the monopolization of the industry, in addition to the quantitative structure of enterprises, it is necessary to analyze the distribution of their income depending on the size. Therefore, accordingly, such a distribution is given not only depending on income, but also taking into account the number of employees. The average growth rate of the number of entities, their income and the number of employees according to the size of enterprises were calculated. Trends in the development of construction companies are studied, their features, typical risks and threats, which are the low level of anti-crisis potential, which is manifested in the reduction of the number of construction companies and the number of employees. It is determined that during the analyzed period there was a steady decrease in the financial stability of enterprises of all sizes. At the same time, the role of small enterprises in the development of the construction sector grew, as, firstly, macroeconomic conditions negatively affected the performance of large enterprises, secondly, changes in the Government structural policy priorities, reforms in the direction of decentralization in general contributed to the activation of small business and private entrepreneurship. Small construction companies increase their revenues, assets, and income much more each year than large and medium-sized ones. It is due to the growth of income indicators and balance sheet items of small enterprises that the whole construction industry is growing, as the representatives of small construction business have the largest share in the trend. The identified patterns proved the need to develop methodological approaches to increase anti-crisis potential and increase viability in a competitive environment not only for small construction companies, but also for medium and large ones.